Once Iron Girls : Essays on Gender by Post-Mao Chinese Literary Women. - Wu, Hui (Rowman & Littlefield Pub. Group, 2010)
Available in English for the first time, Once Iron Girls: Essays on Gender by Post-Mao Chinese Literary Women brings together twenty-five essays by seven critically acclaimed writers, whose fiction and poetry have become classics in modern Chinese literature. Poetic, metaphoric, and sometimes playful and satiric, the essays discuss the material reality wherein Chinese women live and function. Reflecting on their experiences under Mao and in post-Maoist China, these essays vividly demonstrate that, despite equality of the sexes being the official position and women working equally demanding job.